Immunogenicity and safety of tixagevimab-cilgavimab for COVID-19 pre-exposure prophylaxis in immunocompromised 20 to <40 kg children and adolescents: A pilot, prospective, open-labeled study - Jassada Buaboonnam; Supattra Rungmaitree; Nuntawan Piyaphanee; Sirirat Charuvanij; Onsiri Pitisuttithum; Katherine Copeland; Chatkamol Pheerapanyawaranun; Laddawan Jansarikit; Suvimol Niyomnaitham; Kulkanya Chokephaibulkit (Human Vaccines & Immunotherapeutics)
We evaluated the immunogenicity of 300 mg Tixagevimab-Cilgavimab in immunocompromised children and adolescents who weighed 20 to >40 kg. Six to 18-year-old participants were divided into two groups by body weight and received 300 mg (20 to <40 kg) and 600 mg (≥40 kg) Tixagevimab-Cilgavimab, respectively. Anti-SARS-CoV-2 receptor-binding domain IgG concentrations and pseudovirus neutralizing antibody (NAb) titers were measured at 4, 12, and 24 weeks after administration and compared with reference data from healthy Thai children at 2 weeks after three BNT162b2 vaccinations. Of 59 participants, 49.2% were female, with a median (IQR) age of 12 (9, 15) years; 16 (27.1%) had cancer. NAb titers (95% CI) for the ancestral Wuhan strain were comparatively high for both dosing regimens (16363.2 [13765.9, 19450.5] vs 17768.3 [15539.5, 20316.9] in 20 to <40 kg and ≥40 kg participants, respectively) and significantly higher than reference titers (P < 0.001 for both). NAb titers for Omicron BA.4/5 were on par with the reference for both dosing regimens. Adverse events were mild, well tolerated, and slightly more prevalent in ≥40 kg participants who received full-dose Tixagevimab–Cilgavimab. Minimal waning in anti-RBD IgG concentrations, comparable to the reference, was observed at 12 and 24 weeks after Tixagevimab-Cilgavimab administration for both regimens. We concluded that half-dose Tixagevimab-Cilgavimab in 20 to <40 kg participants generated equivalent antibodies to standard doses in ≥40 kg participants and significantly higher antibodies than three-dose BNT162b2 vaccination. Further study of monoclonal long-acting antibodies in larger cohorts and <6-year-old children are warranted.